(untitled) (Journal of Informatics and Mathematical Sciences, 2024)
In this article, we investigate the effect of rotation on plane harmonic waves in an isotropic homogeneous micropolar elastic solid with rotation having uniform angular velocity. It is observed that two sets of coupled dilation and shear waves are propagating with distinct speeds. Out of these, only two shear waves are propagating without elasticity and without micropolarity and two dilation waves are propagating with elasticity and without micropolarity. All these waves are dispersive in nature and affected by the rotation of the medium. It is interesting to observed that harmonic plane waves are not allowed to propagate in high rotating solids. Numerical example have been performed to discuss the behaviour of the speed of the waves.